The relationships between family, financial reason, self-esteem, and career decision making among undergraduates in Jigawa State, Nigeria - Yunusa, Salisu; Wan Jaafar, Wan Marzuki; Ismail, Asmah; Wan Othman, Wan Norhayati (Secholian Publication, 2022)
The study assesses the relationship between career decision-making and family, financial reasons, and self-esteem among undergraduates in Jigawa state, Nigeria using a quantitative correlational research design of the 1,200 undergraduates from Sule Lamido University and Federal University Dutse who made up the population of the study, 373 undergraduates were randomly sampled for the study. Instruments used are: Factors influencing undergraduate students' career decision-making questionnaire and a career decision-making self-efficacy short-form questionnaire. Structural Equation Modelling (SEM) by using Smart Partial Least Squares (Smart-PLS3) was used to analyse the data in line with the hypotheses. The results show that family and financial reasons are positively significant in career decision making among undergraduates. Decisions about family and career (t = 4.300), (β= 0.225), and (P=0.000). With (t = 2.047), (β =0.102), and (P=0.041), the second most significant paths are financial reasons and career decision making. Thus, schools, government agencies, and non-profit organisations should provide scholarships to deserving students so that they can follow their chosen occupations. Students should be exposed to job information and coaching by the school administration in order to assist them in choosing good and realistic career choices. To help minimise the influence of stakeholders on students' career aspirations, school leaders should engage with the counselling unit in schools to provide career workshops for students and parents.